Children Belonging to “No One”: Learners Trapped in Strained and Suspicious Relationships - Winniefridah Matsa (Springer, Cham, 2023)
Migrants’ children experienced a trialogue of neglect and marginalisation. Among teachers, parents and caregivers no one take the full responsibility for neither care or think it is a responsibility to be shared. Each group drew narrow demarcations for its responsibility. To teachers, their role is to teach and ensure learners abide to school rules. To caregivers, theirs is to stay with children and ensure they wake up to school every day. They also facilitate use of provisions sent by migrant parents. Migrant parents send remittances for schooling and basic needs and leave other issues of schooling to caregivers and teachers. There is lack of parent–teacher partnership and shared responsibility between the teachers, parents, caregivers and the community at large. The role of a teacher as loco-parentis and the triad of participant in care of the children are neglected. Migrants’ children are viewed as burdensome to teachers and caregivers. They belong to no one when it comes to schooling, child development and care. In fact, there is a lot of finger-pointing and responsibility shifting as well as blame shifting that strain relations of the trio. Strained relations have detrimental effects on schooling and learning environment. Children are alone in the journey of life and schooling.